Factors influencing Café hopper’s choice of cafes in Bangkok using the AHP approach: Factors influencing Café hopper’s choice of cafes in Bangkok using the AHP approach - Laohaviraphap, Tila (วารสารวิชาการการท่องเที่ยวไทยนานาชาติ, 2023)
The objective of this study was to determine the factors that contribute to customer satisfaction in café establishments, focusing on café-hoppers in Bangkok, Thailand. The data was collected through a combination of purposive random sampling and snowball sampling with the sample group being individuals who regularly visit cafes. The results showed that the main factor influencing customer satisfaction is price, with a score of 28.24%. However, when considering the sub-factors, Uniqueness of experiences was found to hold the greatest significance, with a score of 10.60%. This was followed by Impression with a score of 10.43%. The study also found that the sub-factors of Giveaway Promotion and cleanliness play an important role in attracting and delighting customers. The findings of this study highlight the importance of considering unique experiences, creating a lasting impression, and maintaining a clean appearance for café owners to attract and retain customers. Café owners should prioritize these factors in their management strategies to increase customer satisfaction and drive long-term success. The study used the Analytic Hierarchy Process (AHP) method to analyze the data collected from the questionnaire survey.